Sibship Analysis to Characterize Alligator Gar Reproductive Contributions in Two Texas Systems. (5th February 2020) - Kreiser, Brian R.; Daugherty, Daniel J.; Buckmeier, David L.; Smith, Nathan G.; Newsome, Eleanor B.
Abstract: We used sibship analysis to further our understanding of Alligator Gar Atractosteus spatula reproductive biology. Quantifying the relative contributions of spawners and spatial patterns of reproduction is important in making management decisions, especially with regard to long‐lived, large‐bodied fish like Alligator Gar, for which exploitation of large females may negatively impact recruitment. Using genetic data from age‐0 fish, we estimated the effective number of breeders ( N b ) and the number of spawning adults ( N S ) at multiple spatial and temporal scales in two Texas systems over a 2‐year period. Analysis of 265 fish collected in 2015 from six sites within an approximately 3, 000‐ha floodplain wetland system on the Trinity River identified no full siblings or half siblings with a probability greater than 0.90. Estimates of N b (24–30) and N S (21–33) were comparable among sites, with low levels of relatedness among individuals within sites. Analysis of an additional 136 age‐0 Alligator Gar collected during 2015 from six other sites distributed over 275 river kilometers downstream of the wetland system revealed similar patterns. Age‐0 fish collected in Choke Canyon Reservoir ( N = 131) in 2015 also demonstrated close correspondence between estimates of N b and N S (54 and 56, respectively). Age‐0 Alligator Gar ( N = 88) were again collected at three sites in the Trinity River system during 2016; results were comparable to those of the previous year, with no evidence of repeat spawning at each site. The similarities we observed between the estimated N b and N S indicated little variance in the number of offspring produced among individual spawners. Because individual spawners appear to contribute somewhat equally to the year‐classes and spawning appears to occur over a broad geographic extent, there is likely little risk of year‐class failure from harvesting a sustainable number of spawning adults.